2017
DOI: 10.1016/j.neurobiolaging.2017.05.026
|View full text |Cite
|
Sign up to set email alerts
|

Sound offset-related brain potentials show retained sensory processing, but increased cognitive control activity in older adults

Abstract: This is the accepted version of Horváth, J., Gaál, Z. A., & Volosin, M. (2017). Sound offset-related brain potentials show retained sensory processing, but increased cognitive control activity in older adults. Neurobiology of Aging, 57,[232][233][234][235][236][237][238][239][240][241][242][243][244][245][246] AbstractIt has been hypothesized that age-related hearing loss is caused not only by peripheral, but also central changes in the auditory system. Many studies utilized event-related potentials (ERPs) e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 94 publications
0
3
0
Order By: Relevance
“…A further study of our research group (Horváth, Gaál & Volosin, 2017) demonstrated additional evidence to enhanced cognitive control in the older adults.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…A further study of our research group (Horváth, Gaál & Volosin, 2017) demonstrated additional evidence to enhanced cognitive control in the older adults.…”
Section: Discussionmentioning
confidence: 62%
“…5.1) which exhibit a negative, CNV-like (Walter et al, 1964) going trend before the onset of each tone. Although we did not analyze this baseline part of ERPs, its presence was demonstrated in numerous studies (Berti & Schröger, 2001;Horváth, 2014a;Horváth, Gaál & Volosin, 2017;Schröger & Wolff, 1998b) utilizing constant SOAs in different oddball tasks. Beside of the regular pace of presentation, a second informative foreperiod also characterized the stimuli in the Study I.…”
Section: Discussionmentioning
confidence: 99%
“…The tsPCAs solutions extracted different factors resembling Ta and Tb components. As far as we know, the components underlying this complex have not been previously studied in participants with MCI, and minimally among CNOA (Horváth, Gaál, & Volosin, 2017), making it difficult to draw any conclusions.…”
Section: Discussionmentioning
confidence: 99%